Upaya Meningkatkan Pengetahuan Agama Melalui Metode Penanaman Nilai Akhlak Pada Anak Kelompok A TK Aisyiah 2 Gisting Kabupaten Tanggamus - Nely Zuraida (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
Early age is the most important age, because at that age it is the beginning of a child's growth and development which leads to the next life. With attention and awareness of children's education from an early age, especially education about religion, it will have a positive impact on their lives. If religious values ​​are firmly ingrained in a child, they will grow and develop with the ability to prevent, ward off and protect themselves from various negative influences. This research is a type of field research with a qualitative descriptive approach. This research attempts to look in depth and explain the implementation of instilling Islamic religious values ​​in early childhood at Kindergarten Aisyiyah 1 Mattoanging Pangkep. The source of data obtained was through people who were observed or interviewed, including foundation administrators, teachers, students, parents and parties involved in the research at TK Aisyiyah 1 Mattoanging Pangkep. Data collection techniques were carried out by means of observation, in-depth interviews and documentation. The values ​​instilled in early childhood education at Kindergarten Aisyiyah 1 Mattoanging are the values ​​of aqidah, shari'ah (worship) and morals. All of this is covered in several materials, namely aqidah, fiqh, morals, Asmaul Husna, daily prayers, selected hadiths, history of Islam and Muhammadiyah, reading the Koran. This means that Kindergarten Aisyiyah 1 Mattoanging has taught all dimensions of Islamic teachings in accordance with Islamic and Muhammadiyah teachings. At Aisyiyah 1 Mattoanging Kindergarten, in instilling religious values ​​in early childhood, we use the methods of storytelling, singing, rhymes, hadith, Islamic history and Muhammadiyah history, as well as habituation or heart start. Kindergarten Aisyiyah 1 Mattoanging has taught all the teachings according to Islamic law along with the guidance of Muhammadiyah teachings.